Association of ADAM17 Expression Levels in Patients with Interstitial Lung Disease. (17th February 2020) - Ge, Jianjian; Tang, Lijian; Mu, Peipei; Zhu, Fuli; Xie, Lian; Tang, Yurong
ABSTRACT: A disintegrin and metalloproteinases (ADAMs) are believed to be involved in the pathogenesis of many fibrosis-related diseases. However, little is known regarding the significance of ADAM17 as a biomarker for interstitial lung disease (ILD). In this study, by using the RT-PCR, western blotting and ELISA, we detected the expression level of ADAM17 in peripheral blood mononuclear cells and serum from idiopathic pulmonary fibrosis (IPF) patients, connective tissue disease associated ILD (CTD-ILD) patients and healthy controls, and correlations between clinical and laboratory parameters were also analyzed. We found that IPF patients and CTD-ILD patients showed higher levels of ADAM17 than healthy controls. Moreover, ADAM17 in IPF patients with acute exacerbation (AE-IPF) was significantly higher than that in stable IPF (S-IPF) patients. Expression of ADAM17 was positively correlated with disease duration and CRP but negatively correlated with diffusing capacity of carbon monoxide (DL CO) and total lung capacity (TLC). Among the CTD-ILD patients, SSc-ILD patients had the highest serum levels of ADAM17 compared with the RA-ILD, SS-ILD and IIM-ILD groups and ADAM17 expression levels were correlated with image grading. In conclusion, this study showed that ADAM17 is highly expressed in ILD patients and is associated with disease activity and severity. Additionally, ADAM17 expression is not only related to the primary CTDs, but also to image grading. ADAM17 may serve as a new biomarker for ILD.